Overcoming the Totaliter Past in Ukraine and Germany: the Experience of Germany and the Challenges to Ukraine - Пикало, Андрій (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
This article is devoted to a review of the main features of the memory policy in Ukraine and Germany through the prism of the annual educational course "The Genocide of Jews in Europe: An Historical Perspective and Approaches to Learning" organized by the Ukrainian Center for the Study of the History of the Holocaust in conjunction with the Museum and the Memorial "House of the Wannsee Conference" with the support of the Embassy of Germany in Ukraine. The article gives an overview of individual museum and memorial objects perpetuating the memory of the victims of totalitarian regimes in Kyiv and Berlin, the socio-political reasons for the formation of modern politics of memory and its evolution in Ukraine and Germany. The results of this study indicate that the German policy of memory is more consistent and consistent, while the Ukrainian one is still under the influence of post-Soviet historical discourse, being in the process of complex and heterogeneous transformations.